Comparative characteristics of the clinical and laboratory features of the primary Sjogren’s syndrome associated with anticentromere antibodies and the “classic” subtype of the disease - B. D. Chaltsev; V. I. Vasiliev; S. G. Palshina; A. V. Torgashina; E. V. Sokol; Yu. I. Khvan; E. B. Rodionova; T. N. Safonova (Научно-практическая ревматология, 2021)
Objective: to compare clinical and laboratory manifestations in 2 groups of patients with primary Sjogren’s syndrome (pSS): with and without anticentromere antibodies (ACA); compare the incidence, clinical and laboratory characteristics of lymphomas in these two groups.Materials and methods. We examined 119 patients with ACA-positive pSS (pSS-ACA+). pSS was diagnosed based on Russian 2001 criteria, systemic sclerosis (SSc) – criteria ACR/EULAR 2013. To diagnose liver diseases, the level of transaminases, alkaline phosphatase and antimitochondrial antibodies (AMA) was determined, as well as liver biopsy. The diagnosis of primary biliary cholangitis (PBC) was established according to the recommendations of the American Association for the Study of Liver Diseases, the Russian Gastroenterological Association and the Russian Society for the Study of the Liver. Lymphomas were diagnosed according to histological, immunohistochemical and molecular studies of affected organs biopsies, according to the classification of the World Health Organization. A combination of pSS and SSc was diagnosed in 37 patients, and they were excluded from further analysis. We compared clinical and laboratory features in patients with pSS-ACA+ (n=82) and ACA-negative pSS (pSS-ACA–, n=64) and characterized lymphomas in the pSS-ACA+ (n = 14) and pSS-ACA– (n=10) groups.Results and discussion. In patients with pSS-ACA+, a later age of disease onset was revealed, the duration of the disease before lymphoma development did not differ. In patients with pSS-ACA+, we found a lower frequency of rheumatoid factor (RF), antibodies to Ro (anti-Ro) and La (anti-La), decreased C3-complement, hypergammaglobulinemia, increased IgG concentration, CRP, increased ESR, leukopenia and anemia. 51.2% of patients with pSS-ACA+ were seronegative for anti-Ro, anti-La and RF. Patients with pSS-ACA+ had a higher frequency of AMA and elevated IgM. The incidence of cryoglobulinemia and paraproteinemia did not differ. The frequency of recurrent parotitis in pSS-ACA+ was significantly lower, there were no differences in the frequency and severity of other signs of salivary and lacrimal gland damage. PBC and epitheliitis of the biliary ducts in patients with pSS-ACA+ were detected significantly more often. Damage to the peripheral nervous system, lungs, hypergammaglobulinemic purpura, arthralgia and autoimmune thyroiditis were significantly more often detected in the group of patients with pSS-ACA–. In the pSS-ACA+ group, Raynaud’s phenomenon was significantly more frequent, mainly with scleroderma-type capillaroscopic abnormalities. There was no difference in the frequency of other signs characteristic of SSc. MALT lymphomas were diagnosed in the study groups with the same frequency. Patients with lymphomas in the pSS-ACA+ group were characterized by significantly higher laboratory activity. All patients with lymphomas in both groups showed persistent parotid salivary gland enlargement. Lymphomas in both groups developed in patients with late stage salivary and lacrimal gland damage, systemic manifestations of pSS in both groups were rare.Conclusion. pSS-ACA+ is an independent subtype of pSS, which has a number of significant clinical and laboratory differences from the “classic” variant of the disease. ACA in pSS are associated with a low frequency of anti-Ro, anti-La, and RF, as well as an increased risk of PBC and limited SSc. MALT lymphomas in the pSS-ACA+ and pSS-ACA– groups developed with the same frequency and were associated with the progression of glandular damage, regardless of the presence of systemic manifestations.